THESAURUS MODELLING OF MODERN LEGAL METALANGUAGE - Matvieieva, Svitlana (International Journal of Research -GRANTHAALAYAH, 2020)
The article deals with the problem of creating thesaurus for the English-Ukrainian parallel legal corpus. Such a corpus enables translators and researchers optimize their work with legal texts and their language units – legal terms, choose the best variants for translations, dictionaries, ontologies, etc. The paper describes the problem of a term conceptual structure, it’s functions, and relations within the special legal texts organized in the sentence-aligned corpus. The author of the manuscript demonstrates the main principles of work with the training parallel legal corpus created by the author.